Development of polyether urethane intravaginal rings for the sustained delivery of hydroxychloroquine - Chen Y; Traore YL; Li A; Fowke KR; Ho EA (Dove Medical Press, 2014)
Yufei Chen,1 Yannick Leandre Traore,1 Amanda Li,1 Keith R Fowke,2,3 Emmanuel A Ho1 1Laboratory for Drug Delivery and Biomaterials, Faculty of Pharmacy, 2Department of Medical Microbiology and Infectious Diseases, 3Department of Community Health Sciences, Faculty of Medicine, University of Manitoba, Winnipeg, MB, Canada Abstract: Hydroxychloroquine (HCQ) has been shown to demonstrate anti-inflammatory properties and direct anti-HIV activity. In this study, we describe for the first time the fabrication and in vitro evaluation of two types of intravaginal ring (IVR) devices (a surfaced-modified matrix IVR and a reservoir segmental IVR) for achieving sustained delivery (>14 days) of HCQ as a strategy for preventing male-to-female transmission of HIV. Both IVRs were fabricated by hot-melt injection molding. Surface-modified matrix IVRs with polyvinylpyrrolidone or poly(vinyl alcohol) coatings exhibited significantly reduced burst release on the first day (6.45% and 15.72% reduction, respectively). Reservoir IVR segments designed to release lower amounts of HCQ displayed near-zero-order release kinetics with an average release rate of 28.38 µg/mL per day for IVRs loaded with aqueous HCQ and 32.23 µg/mL per day for IVRs loaded with HCQ mixed with a rate-controlling excipient. Stability studies demonstrated that HCQ was stable in coated or noncoated IVRs for 30 days. The IVR segments had no significant effect on cell viability, pro-inflammatory cytokine production, or colony formation of vaginal and ectocervical epithelial cells. Both IVR systems may be suitable for the prevention of HIV transmission and other sexually transmitted infections. Keywords: intravaginal delivery, matrix system, reservoir system, polymeric drug carrier, drug release, microbicide, HIV/AIDS